Appropriate Technology of Organic Waste Composting with Activator Bioinokulen Rumen Cow Em4 and Em4 - Sunaryo (Institute of Medico-legal Publications Pvt Ltd, 2021)
Intruduction:The waste problem in Indonesia is the large amount of garbage waste, the lack of landfills andwaste processing facilities, resulting in a source of pollution and endangering health. In Ponorogo Regencyin the last three years, garbage has accumulated reaching 149 m3 / day with a percentage of the amountof organic waste amounting to 44.76%. Methods: This type of research is True Experimental, Posttest-Only Control design. The study used 80 ml cattle rumen activator, 80 ml EM4 activator, compost mixtureactivator with 60 ml EM4 + 20 ml livestock rumen activator mixture and 20 ml EM4 + 60 ml cattle rumenactivator, and without activator (control) assessed the level of compost maturity and for tested the NPKlevels and the C / N ratio. The raw material is 3 kg of organic waste with 5 times replication, so that 25fruit samples are needed and 75 kg of organic waste material. Results: The results showed that the compostconcentration was the same as the activator cattle rumen 80 ml, 80 ml EM4, and 60 ml EM4 + 20 ml cattlerumen ripened faster with an average time of 17 days. The results of the measurement of chemical qualitycompost have the best chemical content of SNI 19-7030-2004 compost activator 60 ml + 20 ml EM4 cattlerumen. Conclusions: The conclusion of research on the composting process of waste to be more effectiverequires an activator material. In addition to the activator material, it is necessary to pay attention to thequality of the activator material.